Elucidation of young adults' relationships to forests in northern Sweden using forest story cards. Issue 7 (3rd October 2017) - Kronholm, Thomas; Staal Wästerlund, Dianne
ABSTRACT: As Swedish family forests' owners are ageing, large proportions of ownership will soon be transferred to new owners. However, little is known about forest-related views and expectations of the younger generations. Since forests are economically, ecologically and socially important in Sweden there is increasing interest in elucidating their perceptions and intentions. This paper addresses this issue by exploring young adults' relationships with forests during childhood, current attitudes toward forests and forestry, and their future hopes and intentions regarding forests. Results of focus group sessions with young adults in northern Sweden, using Forest Story Cards to aid the discussions, show that their relationships with forests are intimately connected to their home environment and family matters. Their selections and comments indicate that both their current relationships and childhood experiences of forests are strongly linked to recreational activities, while they are less familiar with forestry operations. The youths appear to have consistently positive attitudes toward and value forests, but their attitudes toward forestry are more diverse, encompassing both positive and negative associations. They also regard environmental aspects of forests and the possibility to offer their children the same forest relationship they enjoyed as important issues for the future.